تحديات العفة والتعفف والاستعفاف في العصر الرقمي: دراسة قرآنية وحديثية ونفسية لآثار وسائل التواصل الاجتماعي - Klaina, Mekki; Kmichou, Halima (International Journal of Humanities, Education, and Social Sciences, 2025)
The importance of this topic lies in the role of religious awareness in promoting ethical values among individuals and communities, and its profound impact on shaping social and moral concepts that contribute to building a stable society. Therefore, this research aims to explore the impact of religious awareness on individuals' behaviours and perceptions of ethical values, as well as how various media contribute to reinforcing these values. The research problem revolves around the following question: Can religious awareness bring about a real and tangible change in individuals' behaviours and perceptions towards ethical values in the contemporary world? The methodology followed in this research is descriptive and analytical, where we examined the verses and prophetic sayings related to the topic in order to explore their meanings and implications for protecting individuals and communities psychologically, physically, socially, economically, and politically. Data collection was also carried out through questionnaires and surveys to determine the impact of religious awareness on individuals' ethical values. The key findings show that religious awareness plays a pivotal role in enhancing ethical values. It was confirmed that individuals exposed to religious content adopt more positive behaviours and values in their daily lives. Additionally, various media outlets, such as religious speeches and videos, significantly contribute to shaping and changing moral attitudes. In conclusion, the research highlights the importance of religious guidance as an effective tool in achieving moral change and enhancing values within society.